The utility of nursing instruments for daily screening for delirium: Delirium causes substantial functional impairment. Issue 3 (June 2020) - Bode, Leonie; Isler, Florian; Fuchs, Simon; Marquetand, Justus; Petry, Heidi; Ernst, Jutta; Schubert, Maria; Garcia Nuñez, David; von Känel, Roland; Boettger, Soenke
Abstract: Objective: Nursing assessments have been recommended for the daily screening for delirium; however, the utility of individual items have not yet been tested. In a first step in establishing the potential of the electronic Patient Assessment-Acute Care (ePA-AC) as such, the impact of delirium on the functional domains was assessed. Method: In this prospective observational cohort study, 277 patients were assessed and 118 patients were delirious. The impact of delirium on functional domains of the ePA-AC related to self-initiated activity, nutrition, and elimination was determined with simple logistic regressions. Results: Patients with delirium were older, sicker, were more commonly sedated during the assessment, stayed longer in the intensive care unit (ICU) and floors, and less commonly discharged home. A general pattern was the loss of abilities and full functioning equivalent to global impairment. For self-initiated mobility, in and out of the bed sizable limitations were noted and substantial inability to transfer caused friction and shearing. Similarly, any exhaustion and fatigue were associated with delirium. For self-initiated grooming and dressing, the impairment was greater in the upper body. Within the nutritional domain, delirium affected self-initiated eating and drinking, the amount of food and fluids, energy and nutrient, as well as parenteral nutrition requirement. In delirious patients, the fluid demand was rather increased than decreased, tube feeding more often required and dysphagia occurred. For the elimination domain, urination was not affected — of note, most patients were catheterized, whereas abilities to initiate or control defecation were affected. Significance of results: Delirium was associated with sizable impairment in the level of functioning. These impairments could guide supportive interventions for delirious patients and perspectively implement nursing instruments for delirium screening.